Assessing Political Literacy Among University Students in Interpreting International News - Andrean Mardohar Sitanggang, Joys; Amanda Sabrina, Nabilah; Hartati, Rita (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study examines the political literacy levels of 30 English Literature students at the State University of Medan, focusing on their ability to navigate, interpret, and critically evaluate international news. Using a qualitative approach, data were collected through a semi-structured questionnaire addressing key factors such as media literacy, civic engagement, and critical thinking. The findings reveal that only 30% of the students demonstrated good political literacy, characterized by consistent fact-checking and critical evaluation of news sources, while 70% exhibited moderate to poor literacy. Key challenges include over-reliance on social media, limited civic participation, and a lack of understanding of political structures. Additionally, only 23% of students correctly identified factual and fake news items, underscoring gaps in media literacy. These results highlight the need for targeted interventions, such as media literacy workshops, enhanced political education, and increased opportunities for civic engagement. By addressing these gaps, the study aims to foster a politically literate and engaged generation of university students.